GAS INSULATED SWITCHGEAR - CHO SUNG JOO; SONG TAE HUN (2023)
The present invention relates to a gas-insulated switchgear. The gas-insulated switchgear according to an embodiment of the present invention comprises: an outer casing having an accommodation space; a fixed contact point fixed within the accommodation space; a movable contact point provided to make or break contact with the fixed contact within the accommodation space; and a fixed conductor unit supporting the fixed contact point within the accommodation space. The fixed conductor unit includes: a fixed conductor fixed to the outer casing; a plurality of joint members connected to the fixed conductor and the fixed contact point, and interconnected to form a predetermined angle with each other; and a plurality of fastening members penetrating and coupling the plurality of joint members, wherein the angle formed by the plurality of joint members can be adjusted. Therefore, the durability of the gas-insulated switchgear can be enhanced. 본 발명은 가스 절연 개폐장치에 관한 것이다. 본 발명의 일 실시 예에 따른 가스 절연 개폐장치는 수용공간을 구비하는 외함;과, 상기 수용공간에 고정되는 고정접점;과, 상기 수용공간에서 상기 고정접점에 접촉 또는 접촉해제 되도록 제공되는 가동접점; 및 상기 수용공간에서 상기 고정접점을 지지하는 고정도체유닛;을 포함하고, 상기 고정도체유닛은, 상기 외함에 고정되는 고정도체;와, 상기 고정도체와 상기 고정접점에 연결되며, 상호 일정 각도를 형성하도록 상호 연결되는 복수의 관절부재; 및 복수의 상기 관절부재를 관통하고, 복수의 상기 관절부재를 결합하는 복수의 체결부재;를 포함하고, 복수의 상기 관절부재가 형성하는 각도가 조절되게 제공될 수 있다.